Knowledge management for talent development & retention: an empirical study of professionals in financial sector of Asia - Osman-Gani, Aahad M. (Academy of Human Resource Development, 2010)
Talent development (TD) and retention issues are becoming increasingly challenging for organizational leaders in today‟s competitive business environment. The Knowledge Management (KM) issues relevant to TD are also receiving more attention among researchers and practitioners. However, not much empirical research was found on the use of KM tools and interventions for developing & retaining talents. Findings from this study can help organizations identify more appropriate KM strategies to better develop & retain talents. HRD researchers may use the empirical findings to develop future research agenda in this area.